Sources of Growth in the Democratic Republic of the Congo : A Cointegration Approach - Cinyabuguma, Matthias (IMF Working Papers; Working Paper ;, 2004)
The paper investigates the sources of growth in the Democratic Republic of the Congo since 1960 and evaluates the relative importance of total factor productivity growth and factor accumulation, using a cointegration method and a growth accounting framework. The main findings confirm that poor economic policies and bad governance (through their effects on total factor productivity and capital accumulation) contributed to the country's economic decline during the 40-year period, 1960-2000. Looking forward, the paper finds that the right policies are being put in place to pave the way for a restoration of economic growth.